An Evaluation of the Stabilization Properties of Equalization in Canada - Robin Boadway; Masayoshi Hayashi (Queen's University, Department of Economics, 2003)
The Canadian system of equalization is designed to address differences in revenue-raising capacity across provinces, basing a province's entitlements on its actual tax bases. However, since it does so on a year-on-year basis, the standard against which a given province's equalization entitlements are calculated fluctuates from year to year with all provinces' tax bases and tax rates. The consequence is that, while the redistribution function is fulfilled annually, the stability of provincial revenues suffers. The evidence we present indicates that, at least for the three revenue categories we examine, the equalization system can actually be destabilizing, thereby imposing on provinces variability in their potential revenue streams that exceeds what would exist in the absence of equalization.
Keywords: H77; 330; Intergovernmental Transfers; Equalization; Stabilization; Interregional Redistribution; Finanzbeziehungen; Kanada